Multitrait Pseudomonas sp. isolated from the rhizosphere of Bergenia ciliata acts as a growth-promoting bioinoculant for plants - Thakur, Rahul; Srivastava, Sudhakar; Yadav, Saurabh (Frontiers in Sustainable Food Systems, 2023)
Multifunctional plant growth-promoting bioinoculants are used to enhance growth, harvest yields, and add economic value to agricultural crops. In this study, such bioinoculant, BC-II-20 (Pseudomonas sp.), was isolated from the rhizospheric soil of a medicinal plant Bergenia ciliata from the Garhwal Himalayas, Uttarakhand, India. After characterization, supplementation with Pseudomonas sp. was used to study growth stimulation in a commercially important medicinal plant, Andrographis paniculata (Kalmegh), and it depicted enhanced physiological growth parameters under controlled conditions. Bacterial seed priming and also supplementation led to early and increased germination and plants displayed better vegetative growth during the entire growth stages. Early initiation of flowers and the appearance of pods occurred in inoculated plants, ultimately leading to the reduction in the life cycle of the plant. At the time of harvesting, there was an increase in the physiological parameters such as shoot length (38%), root length (14%), fresh weight (57%), dry weight (60%), number of panicles, and root branching. Photosynthetic efficiency was also higher, and ultimately, overall plant growth was improved by bacterial inoculation. The eco-friendly and sustainable use of this bioinoculant will provide an alternative to harmful chemical fertilizers and has become increasingly important. In conclusion, we reported a promising bioinoculant having plant growth-promoting traits, which promotes growth and development in A. paniculata and may be applied to other plants also.